(untitled) (Altre Modernità, 2025)
For Philip Roth’s Italian readers, Vincenzo Mantovani –thanks to his eighteen translations, which almost make him Roth’s sole interpreter since the rediscovery of American Pastoral (published in Italy in 1998) – is practically a synonym of the American novelist’s voice in the peninsula. Roth’s Italian wide success has produced a keen critical attention, much diversified in its methods, goals, and language (see Masiero, Simonetti, Manera Sambuy, Samerini, to name just a few). A study of Mantovani’s huge and fascinating archive allows us today to gauge from an unusual point of view the American master’s inevitable and irresistible rise, intersecting chronology (Mantovani, his peer, faithfully followed and reviewed Roth’s literary career from the 1960s) and authorship. Roth’s novels, then, become part of a larger critical activity – a sixty-year uninterrupted arc of professional reading of majestic proportions, within which Roth’s ‘Italian’ voice intersects other dimensions of the Anglo-American 20th- and 21st-century novel – from canonized classics such as Hemingway, Faulkner and Henry Miller, to post-WWII contemporary masters (Vonnegut, Bellow, Malamud, Rushdie), to underappreciated novelists (Gaddis), as well as other major figures of American fiction (Richard Ford, Louise Erdrich). A translator-writer-critic – Mantovani – who rendered Roth successfully into Italian within the context of a much wider intercultural dialogue.